2018
DOI: 10.3389/fpsyg.2018.01035
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Non-symbolic and Symbolic Numerical Representations and Their Associations With Mathematical Ability

Abstract: Most empirical evidence supports the view that non-symbolic and symbolic representations are foundations for advanced mathematical ability. However, the detailed development trajectories of these two types of representations in childhood are not very clear, nor are the different effects of non-symbolic and symbolic representations on the development of mathematical ability. We assessed 253 4- to 8-year-old children’s non-symbolic and symbolic numerical representations, mapping skills, and mathematical ability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(119 reference statements)
3
13
2
1
Order By: Relevance
“…Among both matched peer participant groups in our study, we found that MC N and TEMA-3 partial correlations (.29 or .56 in our verbal-or MC N -matched peers, respectively) were similar to effect sizes reported among other samples of young children~.28 [31] to .52 [33]. In contrast, the partial correlation between MC N and the TEMA-3 observed in girls with TS (.20) did not meet our significance threshold, and a smaller effect size compared to the of MC N and TEMA-3 correlations reported in other studies of mathematics skills in early childhood (e.g., [31,33,68,69]). On the one hand, these findings may suggest that there is nothing unique about the MC N and TEMA-3 correlation in TS, because a correlation of .20 approaches those earlier reported levels; on the other hand, these correlations among girls with TS were weaker relative to the other groups, did not reach statistical significance when correcting for multiple comparisons, and thus may be suggestive of a disparate trend in the TS group compared to peers.…”
Section: Mathematics Scoressupporting
confidence: 87%
“…Among both matched peer participant groups in our study, we found that MC N and TEMA-3 partial correlations (.29 or .56 in our verbal-or MC N -matched peers, respectively) were similar to effect sizes reported among other samples of young children~.28 [31] to .52 [33]. In contrast, the partial correlation between MC N and the TEMA-3 observed in girls with TS (.20) did not meet our significance threshold, and a smaller effect size compared to the of MC N and TEMA-3 correlations reported in other studies of mathematics skills in early childhood (e.g., [31,33,68,69]). On the one hand, these findings may suggest that there is nothing unique about the MC N and TEMA-3 correlation in TS, because a correlation of .20 approaches those earlier reported levels; on the other hand, these correlations among girls with TS were weaker relative to the other groups, did not reach statistical significance when correcting for multiple comparisons, and thus may be suggestive of a disparate trend in the TS group compared to peers.…”
Section: Mathematics Scoressupporting
confidence: 87%
“…It has been shown repeatedly that basic number skills form the foundations for learning more complex mathematical skills (Butterworth, 2005;Jordan et al, 2009;Li et al, 2018), and early numerical skills predict later achievement in mathematics (Zhang et al, 2017;Blume et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional and longitudinal studies have looked at numerical magnitude processing (NMP) and working memory (WM) as possible domain-specific and domain-general cognitive precursors of children's mathematics performance and development (e.g. Alloway & Alloway, 2010;De Smedt et al, 2013;Friso-van den Bos et al, 2013;Kroesbergen & van Dijk, 2015;Li et al, 2018;Toll et al, 2016). Both NMP and WM have been…”
Section: Introductionmentioning
confidence: 99%